Dinamika Proses Legislasi Perda Kabupaten Sidoarjo No. 1 Tahun 2025 Tentang BPR Delta Artha - Wahyu Agung Nuril Fahmi; Kurniawan Sugiarto (Cattleya Darmaya Fortuna, 2025)
This study discusses the process of amending Sidoarjo Regency Regional Regulation (Perda) No. 8 of 2021 into Perda No. 1 of 2025 concerning BPR Delta Artha. The main issues addressed are the urgency of regulatory adjustment in accordance with the Law on the Development and Strengthening of the Financial Sector (UUP2SK) and the need to enhance the competitiveness of BPR Delta Artha as a regional bank. This research employs a narrative qualitative approach to provide an in-depth depiction of the dynamics, experiences, and processes involved in the amendment of the regulation through document studies, interviews, and public policy analysis based on William N. Dunn’s framework, which includes problem identification, impact forecasting, recommendations, and policy evaluation. The results indicate that the amendment process was carried out quickly and in a structured manner without the formation of a Special Committee, driven by community needs and instructions from the Ministry of Home Affairs. The main implications of this change are the expansion of BPR’s functions, the change in nomenclature to Bank Perekonomian Rakyat (People’s Economy Bank), and the improvement of financial access and support for MSMEs in Sidoarjo.